Regulating the Catalytic Dynamics Through a Crystal Structure Modulation of Bimetallic Catalyst. Issue 8 (15th January 2020) - Park, Mihui; Liang, Chaoping; Lee, Tae Hyung; Agyeman, Daniel Adjei; Yang, Junghoon; Lau, Vincent Wing‐hei; Choi, Sang‐Il; Jang, Ho Won; Cho, Kyeongjae; Kang, Yong‐Mook
Abstract: The surface of solid catalysts is one of the most important factors where the interface with reaction products governs the reaction kinetics. Herein, the crystal phase of palladium–copper nanoparticles (PdCu NPs) is controlled to modulate their surface atomic arrangement, which will govern the growth dynamics of discharge products on their surfaces and thus the catalytic performances in non‐aqueous lithium–oxygen (Li‐O2 ) batteries. First‐principles calculations and experimental validations reveal that homogeneous nucleation and distribution of discharge products are observed on the surface of body‐centered cubic PdCu NPs, promoting the oxygen reduction/evolution reaction (ORR/OER) activities in Li‐O2 batteries. However, the agglomerates formed on the surface of its face‐centered cubic homologue deteriorates ORR/OER activities, which worsen the battery performances. For the first time, this work theoretically and experimentally demonstrates how the crystal phase modulation regulates the nucleation behaviors and growth dynamics of discharge products for ORR/OER. Abstract : The modified surface structure according to crystal structure of bimetallic PdCu catalysts modulates growth dynamics of reaction products reaction kinetic of oxygen reduction/evolution reaction as well. The intermetallic ordered bcc PdCu forms an efficient interface due to higher surface energy, leading to superior catalytic activity and battery performance.